Validation of force fields of rubber through glass-transition temperature calculation by microsecond atomic-scale molecular dynamics simulation - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Journal of Physical Chemistry B, 2016)
Microsecond atomic-scale molecular dynamics simulation has been employed to calculate the glass-transition temperature (T-g) of cis- and trans-1,4-polybutadiene (PB) and 1,4-polyisoprene (PI). Both all-atomistic and united-atom models have been simulated using force fields, already available in literature. The accuracy of these decade old force fields has been tested by comparing calculated glass-transition temperatures to the corresponding experimental values. T-g depicts the phase transition in elastomers and substantially affects various physical properties of polymers, and hence the reproducibility of T-g becomes very crucial from a thermodynamic point of view. Such validation using T-g also evaluates the ability of these force fields to be used for advanced materials like rubber nanocomposites, where T-g is greatly affected by the presence of fillers. We have calculated T-g for a total of eight systems, featuring all-atom and united-atom models of cis- and trans-PI and-PB, which are the major constituents of natural and synthetic rubber. Tuning and refinement of the force fields has also been done using quantum-chemical calculations to obtain desirable density and T-g. Thus, a set of properly validated force fields, capable of reproducing various macroscopic properties of rubber, has been provided. A novel polymer equilibration protocol, involving potential energy convergence as the equilibration criterion, has been proposed. We demonstrate that not only macroscopic polymer properties like density, thermal expansion coefficient, and T-g but also local structural characteristics like end-to-end distance (R) and radius of gyration (R-g) and mechanical properties like bulk modulus have also been equilibrated using our strategy. Complete decay of end-to-end vector autocorrelation function with time also supports proper equilibration using our strategy.